2008
DOI: 10.1071/ah080684
|View full text |Cite
|
Sign up to set email alerts
|

Few urban–rural differences in older carers' access to community services

Abstract: To examine perceived adequacy of access to information and services, and perceived quality of health and community services, among older female carers across rural and urban areas primary data were collected as part of the ongoing Australian Longitudinal Study on Women's Health (ALSWH). In all, 306 women in their 70s who had family caregiving roles responded to a nested substudy of the ALSWH. There were few reported differences between urban and rural older carers in their access to health and community servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This reflects targeting of services to special needs groups, as well as perhaps facilitation of access to services in rural areas through closer community networks [22] and variations in assessment practices [23]. Similar factors, as well as higher rates of disability, may contribute to higher rates of HACC service use among Indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects targeting of services to special needs groups, as well as perhaps facilitation of access to services in rural areas through closer community networks [22] and variations in assessment practices [23]. Similar factors, as well as higher rates of disability, may contribute to higher rates of HACC service use among Indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…Some carers require support and education on practical skills to assist with their caregiving role and access to support services is oftentimes limited due to complex eligibility criteria (Essue et al, 2010). This is complicated further by the low levels of assistance to primary caregivers and awareness of many existing community services for carers and their recipients (Lucke et al, 2008;Vecchio, 2008b). Users of different support services may also have differing levels of unmet support needs.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing participation among caregivers could be challenging because research has demonstrated a lack of willingness to participate among patients who have not yet experienced the service . In addition, caregivers of frail, older patients tend not to use many of those services available to them, and further work is needed to understand how to encourage participation …”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, caregivers of frail, older patients tend not to use many of those services available to them, and further work is needed to understand how to encourage participation. 23,24 At present, there is currently no existing theoretical framework which links caregivers' stress with their intentions to participate in health services. Furthermore, there are no quantitative studies that have investigated caregivers' willingness to participate in HMR.…”
Section: Introductionmentioning
confidence: 99%